Social responsibility, a key dimension in developing a sustainable higher education institution: The case of students' motivation - Cosmin-Ionuț Imbrisc\~a; Sorin-George Toma (Amfiteatru Economic Journal, 2020)
Over time, sustainability and social responsibility have become key concepts at macro-level, meso-level and micro-level, and in various domains such as business and higher education. The paper aims to explain the close relationship between the two concepts in higher education, and to identify and analyse the various factors that motivate or impede students from becoming involved in social responsibility activities. The information was gathered by using a stratified sampling method from the students enrolled at a Romanian higher education institution, the Faculty of Business and Administration University of Bucharest. Then, the information was processed through the factorial analysis in order to identify the underlying unobserved variables and how they relate to students' decision to participate in social responsibility activities. Finally, a logit regression analysis led to the main results that show that personal values are the main motivators, whereas structural and interpersonal barriers are the main inhibitors. The paper also demonstrates that the social responsibility activities contribute to the development of sustainable higher education institutions through the active engagement and participation of their students.
Keywords: M14; Q56; 330; sustainability; social responsibility; sustainable higher education institution; students; motivation; sustainable development